The impact of grassland renovation on sward composition and quality under organic farming conditions - Gaweł, Eliza; Grzelak, Mieczysław (Polish Journal of Agronomy, 2019)
The aim of the research carried out in the organic field was the valuation of influence of renovation of sward with legume-grass mixtures on the quality of fodder obtained. The two-factor field experiment was conducted in 2013–2016 in the Agricultural Experimental Station IUNG-PIB Grabów (Mazowieckie voivodeship, Poland). It compares two ways of renovating grassland: A – after ploughing and B – after superficial disturbance of the soil to the depth of 5 cm with a compact harrow, as well as three legume-grass mixtures (Krasula mixture + 3.5 kg of white clover, Cent 4, and original mixture). The field experiment evaluated: dry matter yield, share of legumes and grass species in the sward of mixtures, content of: protein, P, K, Ca, Mg and fiber fraction, relative nutritional value and feed unit for lactation, protein value of dry matter, and the filling units for lactation. The method of renovation of grassland and the species composition of the sward did not affect the quality of the fodder obtained or its energy and filling value. A decrease of sward abundance in total protein under the influence of increasing percentage of grasses in sward of mixtures, was found. Medium-quality fodder was obtained, which in the first year of use was rated as class III and in the following years as class IV of relative feed value.